A new species of the genus Tenuipalpus (Prostigmata: Tenuipalpidae) with remarks on a conceivable ovipositor in flat mites - Flechtmann, Carlos H.w.; Noronha, Aloyséia C.s. (Zootaxa, 2013)
A new mite species Tenuipalpus bacuri sp. nov. (Prostigmata: Tenuipalpidae) from Platonia insignis Mar. (Clusiaceae) is described from Brazil (Para). Setal notation are as in Mesa et al. 2009; all measurements are in micrometres.